Teaching Reading Comprehension of Explanatory Text by Using Directed Reading and Thinking Activity (DRTA) - Nadya Wulandari; Nurhaedah Gailea; Yusti Fargianti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to improve the reading skills of fifth grade students of SDN Warnasari using Directed Reading and Thinking Activities as a learning method in English subjects. This reserach used classroom action research and conducted in three cycles. Methods used to collect data include documentation, observation, and test. The increase in students' reading comprehension can be seen from classical completeness which shows that from one cycle to the next, classical completeness scores increased from 58% in cycle I to 84% in cycle II and increased to 100% in cycle III. The average student score in cycles I and II also increased, from 76.4 in cycle I to 82.10 in cycle II and 86.31 in cycle III. The conclusion is the application of the Directed Reading and Thinking Activity method can improve students' reading skills in English subjects in class V at SDN Warnasari for the 2023/2024 academic year.